The impact of work stress towards job performance among managers in private sectors in Kota Kinabalu Sabah - Marion Anthony (2008)
The problem measure in this research is to identify the Impact of work stress towards job performance among managers. This study has put forward five research questions. Firstly what is the level and Impact of work stress on job performance? Second, what is the source of work stress on job performance among managers? Third, what is the relationship between the sources of work stress and job performance? Fourth, what is the function of gender as a moderator between source of work stress and work stress among managers? Fifth, what is the role of work stress as a mediator between work stress and job performance? To answer these research questions, this study has outlined five research objectives. First, to study the level and the Impact of work stress towards job performance. Second, to Identify the source of work stress on job performance among managers. Third, to examine the relationship between work stress and job performance. Fourth, to Identify Impact of gender as a moderator between source of work stress and work stress among managers. Lastly, to examine the role of work stress as a mediator between work stress and job performance. This study is conducted in three private companies; Suria capital Holdings Berhad, Warisan Hartanah Sdn. Bhd and Sabah Bank Development Berhad. The respondents are 105 middle to top management level/managers from those companies. Altogether six hypotheses are forwarded to be tested using Statistical Package Social Sciences (SPSS) Version 14.0. The test conducted had Indicate that: I) there is a significant relationship between the sources of work stress towards work stress; II) there Is a significant relationship between sources of work stress and job performance; iii) there is a significant relationship between the impact of work stress and job performance; Iv) gender is not a significant moderating variable between sources of work stress and work stress; v) feelings and behaviour is not a significant mediating variable between sources of work stress and job performance. A number of research limitations are identified and suggestions for future research are proposed.